Requirements engineering : foundation for software quality : 22nd International Working Conference, REFSQ 2016, Gothenburg, Sweden, March 14-17, 2016, Proceedings /: foundation for software quality : 22nd International Working Conference, REFSQ 2016, Gothenburg, Sweden, March 14-17, 2016, Proceedings. (2016) - Unknown
No abstract available